Captive Breeding of Pufferfish (Leiodon cutcutia) from Assam, India - Karmakar, Panchali; Biswas, S.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Background: Leiodon cutcutia has been exploited from its natural habitats which leads to a drastic decline of its natural socks ever since it has been reported its ornamental value. The development of effective breeding protocols, optimal management of environmental conditions, and the use of appropriate hormonal treatments can help stock improvement of the species. Methods: Live specimens were collected from the Meleng River across the Jorhat districts. The maturity cycle was properly studied to determine the breeding season of the species. Acclimatization of the brooder and feeding were done following standard protocol. Breeding trials were conducted by habitat manipulation and also by administering hormonal injections. Findings: Spawning was triggered by simulating habitat conditions of the breeding enclosure and extending daylight hours. The species exhibits sexual dimorphism; the females have white spots on the body and are always larger than the males. Males typically display courtship behaviour such as chasing and circling females. Territorial and aggressive behaviours complicate breeding efforts, requiring careful management of tank mates and breeding pairs. Adhesive eggs were attached to the substratum and males were found to guard the eggs until hatching. The breeding experiment had moderate success. Conclusion: Captive breeding of Leiodon cutcutia presents unique challenges but offers significant benefits for conservation and the aquarium trade.